1978
DOI: 10.1902/jop.1978.49.9.480
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tobacco Smoking on Plaque Development and Gingivitis

Abstract: A study was undertaken to test the hypothesis that patients who smoke tobacco have a more rapid rate of plaque deposition and development of gingivitis than those patients who do not smoke tobacco. Twenty subjects participated in this study, their age range was 17 to 30 years. Ten were smokers and 10 were nonsmokers. After an initial thorough removal of all deposits, oral hygiene measures were stopped for 10 days. On days 3, 7 and 10, plaque levels were evaluated using the Plaque Index and the gingival status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
41
3
7

Year Published

1985
1985
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 15 publications
12
41
3
7
Order By: Relevance
“…Noticed deterioration of oral hygiene among smokers is consistent with previous research (15). Some results showed that long-term smoking causes oral hygiene to deteriorate and it increases the severity of gingival disease (16).…”
Section: Petrušić I Sursupporting
confidence: 90%
See 3 more Smart Citations
“…Noticed deterioration of oral hygiene among smokers is consistent with previous research (15). Some results showed that long-term smoking causes oral hygiene to deteriorate and it increases the severity of gingival disease (16).…”
Section: Petrušić I Sursupporting
confidence: 90%
“…Zbog štetnih utjecaja na slinovnice najprije stradaju doušne žlijezde čija je zadaća izlučivanje seroznog sekreta. Gubitak njihove funkcije kompenziraju podčeljusna i podjezična žli-jezda koje izlučuju mukozni sekret (15). To objašnjava gušću slinu kod pušača.…”
Section: Petrušić I Surunclassified
See 2 more Smart Citations
“…Early in vitro studies using culture-based methods noted that cigarette smoke has a strong inhibitory effect on the growth of Neisseria species (Bardell, 1981;Ertel et al, 1991), while Streptococcus species were less inhibited by cigarette smoke (Bardell, 1981). Additionally, early studies in humans identified decreased Neisseria species on mucosal surfaces of smokers (Colman et al, 1976), and an increased proportion of Gram-positive to Gram-negative bacteria on developing plaques of smokers (Bastiaan and Waite, 1978). Recently, studies with comprehensive oral bacterial profiling in humans have found increased Streptococcus sobrinus and Eubacterium brachy in the saliva of smokers (Belstrom et al, 2014), decreased Neisseria, Porphyromonas and Gemella in oral wash samples from smokers (Morris et al, 2013), enrichment of Megasphaera, Streptococcus and Veillonella, and depletion of Meta-analysis P-values from Kruskal-Wallis tests within each of the four data sets, calculated using Z-score methods.…”
Section: Discussionmentioning
confidence: 99%